The Art of Skill Transfer - Shah, Santosh (Journal of Universal College of Medical Sciences, 2023)
In today's dynamic world, the ability to transfer skills across various domains has become a cornerstone of personal and professional success. As industries evolve and technology advances, individuals who master the art of skill transfer find themselves not only adaptable but also at the forefront of innovation.